Coagulase-negative staphylococcal bacteraemia in cancer patients. Time to positive culture can distinguish bacteraemia from contamination. Issue 9 (2nd September 2018) - Morioka, Shinichiro; Ichikawa, Mika; Mori, Keita; Kurai, Hanako
Abstract: Background: Coagulase-negative staphylococci (CoNS) are the most common contaminants of blood cultures, however, we sometimes have difficulties in determining their clinical significance. It is still controversial that there is a significant difference between the contamination group and the true bacteraemia group in the time to positivity (TTP) of blood cultures. We validated the relationship between a TTP and the presence of CoNS bacteraemia in cancer patients by using an objective, non-judgmental definition for CoNS contamination. Methods: We retrospectively reviewed 175 sets of blood cultures drawn from 95 patients that yielded CoNS from October 2011 to March 2013. We considered as contamination if an isolate of CoNS was identified in one out of multiple sets of blood cultures. We investigated the TTP, the threshold values and corresponding likelihood ratios to distinguish CoNS bacteraemia from contamination. Results: The median TTP in CoNS bacteraemia group was significantly shorter than that in contamination group (14 h 45 min and 20 h 31 min, respectively, p  = .0157). A TTP of ≤16 h had a specificity of 83% for predicting CoNS bacteraemia, and that of >20 h had a sensitivity of 86% for predicting CoNS contamination. Conclusions: We validated that the median TTP in CoNS bacteraemia group was significantly shorter than that in their contamination group, and that a TTP of ≤16 h was associated with CoNS bacteraemia, while that of >20 h was associated with CoNS contamination, if evaluated with an objective, non-judgmental definition for CoNS contamination.